Non-HLA Antibodies in Highly Sensitized Renal Transplant Candidates. (July 2018) - Vittoraki, Angeliki; Markaki, Pavlina; Ioannou, Sofia; Skoumi, Dimitra; Chouliari, Niki; Melissou, Dimitra; Apostolaki, Maria; Iniotaki, Aliki
Abstract : Introduction: Non-HLA allo- and autoantibodies, as are antibodies (abs) against Major-histocompatibility-complex class I–related-chain A (anti-MICA) and angiotensin II type 1 receptor (anti-AT1R), are implicated in rejection and graft failure post renal transplantation. These abs are not detected with the classical crossmatch before transplantation. The aim of this study was to assess the incidence of preformed anti-MICA and anti-AT1R abs in highly sensitized renal transplant candidates (HSP, with %cPRAs>70) as compared to non sensitized patients (%cPRAs<5) awaiting for renal transplantation, in order to define possible additional pre-transplant immunological risk factors. Materials and Methods: In total, 169 renal transplant candidates were tested, including 115 HSP (study group) and 54 non-sensitized patients (control group-CG-pts). Anti- HLA sensitization in HSP vs CG-pts was due to previous transplantation(s) (81 vs 0 pts), pregnancies (25 vs 6 pts) and transfusions (82 vs 10 pts). Blood samples were tested (a) for anti-HLA and anti-MICA antibody specificities by Single Antigen Bead Assay (Luminex, One Lambda) and (b) for AT1R-abs by ELISA (EIA-AT1R kit, One Lambda). For anti-HLA and anti-MICA abs an MFI >1000 was considered as positive. Anti-AT1R-ab levels were classified as low <10U/mL, at risk 10-17U/mL and high>17U/mL. The Chi Square test (Yate's corrected) was used for statistical analysis. Results and Discussion: Broad sensitization against HLA alleles was observed in HSP with 93/115 HSP to exhibit abs against both HLA class I & II loci. More precisely, antibodies against HLA-A, -B, -C, -DRB1, -DQA1, -DQB1, -DPB1 was observed in 83%, 85%, 58%, 82%, 32%, 73% and 32% of the HSP respectively. Anti-MICA-abs were detected in 17/115 (14, 8%) HSP and in 1/54 (1.8%) CG-pts (p=0.02). Anti-AT1R-abs were detected in 44/115 (38, 3%) HSP and 5/54 (9.2%) CG-pts (p=0.0002). The anti-AT1R-abs were detected either in intermediate (n=32, 27, 8%) or high levels (n=12, 10, 4%) in HSP with mean±SD values of 12.3±1.9 and 25.4±10.5 U/ml respectively. The anti-AT1R-ab levels in 4 positive CG-pts were close to cut-off with mean±SD values 11.2±1.5 U/ml while only one patient presented high levels. The presence of anti-AT1R-abs was associated with pregnancies and/or graft loss. All HSP with only transfusion history had low anti-AT1R levels. The presence of anti-MICA-abs was significantly correlated with anti-AT1R-abs (p=0.01). Conclusion: Given the complexity of mechanisms involved in kidney graft rejection, HLA as well as non-HLA pre transplant antibody responses should be taken into account in order to define patients with particular risk for irreversible graft injury. Highly sensitized renal transplant candidates have additional to donor HLA risk factors before renal transplantation. Detection of non-HLA antibodies may be useful in immunological risk assessment pre-transplantation and may help clinicians to establish therapeutic protocols in order to improve graft outcome.